2014
DOI: 10.1093/intqhc/mzu039
|View full text |Cite
|
Sign up to set email alerts
|

Health service accreditation reinforces a mindset of high-performance human resource management: lessons from an Australian study

Abstract: This study reveals that HCOs that pursue highly performing HRM systems use participation in an accreditation program as an opportunity. Their organizational mindset is to use the program as a tool by which to reflect and obtain feedback on their performance so to maintain or improve their management of staff and delivery of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…As noted previously, provision of L&D to develop FLM skills in HRM is not a mandatory requirement of the ACHS survey. Hence, hospitals undertaking such programs would likely be motivated by best practice or performance improvement rather than compliance (Greenfield et al, 2014). Reflecting the pessimistic view of prior research, the research team expected low incidence of HRM L&D for FLMs, even among high performing cases.…”
Section: Developing Ward Managers' Hrm Abilitymentioning
confidence: 99%
“…As noted previously, provision of L&D to develop FLM skills in HRM is not a mandatory requirement of the ACHS survey. Hence, hospitals undertaking such programs would likely be motivated by best practice or performance improvement rather than compliance (Greenfield et al, 2014). Reflecting the pessimistic view of prior research, the research team expected low incidence of HRM L&D for FLMs, even among high performing cases.…”
Section: Developing Ward Managers' Hrm Abilitymentioning
confidence: 99%
“…The impact of accreditation programs on health service organizations and units were examined in 27 studies CASTLE, 2012b;YU, 2012;GUINDO et al, 2012;ABDALLAH et al, 2013;PRONOVOST et al, 2013;SALEH et al, 2013;DAY et al, 2013;ABOU ELNOUR et al, 2014;LEE, 2014;MARONE et al, 2014;MARSHALL, 2014;MBAH et al, 2014;MOHAMMADI;MATIN;RIAHI, 2014;PARTHASARATHY;SUBRAMANIAN;QUAN, 2014;SAGHATCHIAN et al, 2014;SHAW et al, 2014;SONG;LI;ZHOU, 2014;MORAN, 2014;YILDIZ;KAYA, 2014;CARMAN;TIMSINA;SCUTCHFIELD, 2014;EL-JARDALI et al, 2014;GREENFIELD et al, 2014c;WENSING, 2015;RAJAN et al, 2015;ANDIRIC;MASSAMBU, 2015;SISAY et al, 2015;CHEN et al, 2015), including continuous quality improvement, the quality of care and safety of organizational cultures, compliance with external programs guidelines, standardization of care processes, and performance management systems. As observed in a research results, most responding hospitals considered accreditation as a worthy investment due to its effect on enhanced quality and safety culture (SALEH et al, 2013).…”
Section: Organizational Impactsmentioning
confidence: 99%
“…Participation in an accreditation program, in a developing country, the United Arab Emirates, was shown to stimulate and maintain organisational improvements in quality measures within an accreditation cycle [3]. Similarly, in Australia, a developed country, it was demonstrated that the effective functioning of an organisation's HRM system can be enhanced through participation in an accreditation cycle; the caveat being that the motivation for excellence is internal so that the accreditation program reinforces, rather than drives, performance improvements [15]. Whether improvements are maintained across cycles, or are realised in other settings, is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Performance in an accreditation program is reflected in higher levels of clinical performance outcomes [11][12][13][14], the effectiveness of organisational systems, including human resource management (HRM) systems [12,15] or organisational care processes [3,11].…”
Section: Introductionmentioning
confidence: 99%